2015
DOI: 10.1152/ajplung.00025.2015
|View full text |Cite
|
Sign up to set email alerts
|

Proteases in agricultural dust induce lung inflammation through PAR-1 and PAR-2 activation

Abstract: Romberger DJ, Heires AJ, Nordgren TM, Souder CP, West W, Liu X, Poole JA, Toews ML, Wyatt TA. Proteases in agricultural dust induce lung inflammation through PAR-1 and PAR-2 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Notwithstanding, overall, the disulphide-maintained conformation of all of the enzymes due to the 6 conserved cysteines would be expected to expose both common and distinct antigenic sites. Given the demonstrated reactivity of Per a 10-sensitized human subjects in terms of their intradermal response, IgE immunoreactivity and Per a 10-stimulated histamine release by peripheral blood leukocytes [8, 9], it is possible that there may be cross-sensitization to enzymes from all cockroach species and also possibly to mammalian and fish trypsins to which agricultural and fish plant workers are exposed [22, 23]. Whether or not the insect serine proteinases represent significant allergens themselves, the ones we have studied so far all appear to be able to signal via PAR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, overall, the disulphide-maintained conformation of all of the enzymes due to the 6 conserved cysteines would be expected to expose both common and distinct antigenic sites. Given the demonstrated reactivity of Per a 10-sensitized human subjects in terms of their intradermal response, IgE immunoreactivity and Per a 10-stimulated histamine release by peripheral blood leukocytes [8, 9], it is possible that there may be cross-sensitization to enzymes from all cockroach species and also possibly to mammalian and fish trypsins to which agricultural and fish plant workers are exposed [22, 23]. Whether or not the insect serine proteinases represent significant allergens themselves, the ones we have studied so far all appear to be able to signal via PAR2.…”
Section: Discussionmentioning
confidence: 99%
“…Given the demonstrated reactivity of Per a 10-sensitized human subjects in terms of their intradermal response, IgE immunoreactivity and Per a 10-stimulated histamine release by peripheral blood leucocytes, 8,9 it is possible that there may be cross-sensitization to enzymes from all cockroach species and also possibly to mammalian and fish trypsins to which agricultural and fish plant workers are exposed. 23,24 Whether or not the insect serine proteinases represent significant allergens themselves, the ones we have studied so far all appear to be able to signal via PAR2. Thus, all of the enzymes E1, E2 and E3 in isolation would be able to synergize with other allergens in the cockroach extract to trigger the allergic process.…”
Section: Erk 1/2 Via Par2mentioning
confidence: 97%
“…It was discovered that proteolytic cleavage of CCL9 greatly enhances its chemotactic potential [41], suggesting that CCL9 may act as an early response chemokine, responding to local proteolysis that enhances the chemotactic signal. This is of particular interest to our work in that our group has recently demonstrated that HDE is capable of inducing proteolytic cleavage/activation of PAR receptors [42] by HDE. It is therefore possible that CCL9 may be similarly activated in the alveolar space in response to barn dust.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we detected elastase- and trypsin-like activities in aqueous extracts of poultry dust, and found that heat inactivation at 95 °C for 10 min and serine protease inhibitors such as, α1-antitrypsin and soybean trypsin inhibitor suppressed induction of IL-8 mRNA and protein levels in THP-1 monocytic cells (Bandari, S. K., Master’s Thesis, University of Texas Health Science Center at Tyler, 2012). While our studies were in progress, the presence of proteases in the swine barn dust and their effects on the induction of cytokine expression in lung cells and mouse lung via activation of PAR-1 and PAR-2 were reported [ 38 ]. A number of noteworthy points distinguish our studies from the recent report; our studies have independently provided further evidence for the involvement of protease activities in organic dust from an entirely different source, namely poultry, in the induction of inflammatory gene expression in lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%